A 3D finite element analysis of bone tissue in three-unit implant-supported prostheses configurations through varying configuration factors (single-unit and splinted crowns in straight-line and offset configurations) and implant lengths in the maxillary posterior region (Research, Society and Development, 2021)
The objective of the present study was to analyze the stress and microstrain on cortical bone tissue caused by occlusal forces on three-unit implant-supported prostheses placed in the maxillary posterior region through varying configuration factors and implant lengths using 3D finite element analysis. Fifteen three-dimensional models were simulated with the support of the In Vesalius, SolidWorks 2016, and Rhinoceros 4.0 software programs. Each three-dimensional model included a maxillary bone block corresponding to the region from the 1st premolar to the 1st right molar with three EH implants measuring 4.0 mm in diameter, which supported the three-unit metal-ceramic screw-retained prosthesis through varying configuration factors (single-unit and splinted crowns: straight-line and tripod design) and implant lengths (10, 8.5, and 7 mm × Ø4 mm). The FEMAP 11.4.2 program was used to generate the finite element models in the pre- and post-processing phases. Bone tissue was analyzed using Maximum Principal Stress (MPa) and Microstrain (με) maps. The highest stress/microstrain values were observed in oblique loading. In addition, splinting associated with the offset configuration generated improved biomechanical behavior. Furthermore, the association of short implants with longer implants did not exhibit any biomechanical benefits. Moreover, a reduced implant length (i.e., 7 mm) generated unfavorable biomechanical behavior. Splinting was effective in reducing the stress/microstrain on cortical bone tissue, especially when associated with the offset configuration of the implants. Also, an increased implant length decreased the stress/microstrain in the bone tissue, and splinted short implants presented similar biomechanical behavior to short implants associated with longer implants.